The Long Non-coding RNA TMPO-AS1 Promotes Bladder Cancer Growth and Progression via OTUB1-Induced E2F1 Deubiquitination - Zhang, Yeyu; Zhu, Yuxing; Xiao, Mengqing; Cheng, Yaxin; He, Dong; Liu, Jianye; Xiang, Liang; Gong, Lian; Wang, Zhanwang; Deng, Liping; Cao, Ke (Frontiers in Oncology, 2021)
Background: Increasing evidence indicates that long non-coding RNAs (lncRNAs) play crucial roles in cancer tumorigenesis and progression. TMPO antisense RNA 1 (TMPO-AS1) has been found to be involved in several cancers by acting as a competing endogenous RNA. However, the potential roles of TMPO-AS1 in bladder cancer (BC) and the potential interactions with proteins remain poorly understood. Methods: The expression of the lncRNA TMPO-AS1 was evaluated via bioinformatic analysis and further validated by quantitative real-time PCR (qRT-PCR). Loss- and gain-of-function assays were performed to determine the biological functions of TMPO-AS1 in BC cell proliferation, migration, and invasion. Moreover, chromatin immunoprecipitation, Western blotting, and fluorescence in situ hybridization, as well as RNA pull-down, RNA immunoprecipitation, and luciferase reporter assays, were conducted to explore the upstream and downstream molecules interacting with TMPO-AS1. Results: TMPO-AS1 is upregulated in BC. Functional experiments demonstrated that TMPO-AS1 promotes cell proliferation, migration, and invasion in BC and inhibits cell apoptosis in vivo and in vitro. Mechanically, E2F1 is responsible for TMPO-AS1 upregulation. Additionally, TMPO-AS1 facilitates the interaction of E2F1 with OTU domain-containing ubiquitin aldehyde binding 1 (OTUB1), leading to E2F1 deubiquitination and stabilization; therefore, TMPO-AS1 promotes BC malignant phenotypes. Furthermore, rescue experiments showed that TMPO-AS1 promotes BC growth in an E2F1-dependent manner. Conclusions: Our study is the first to uncover the novel TMPO-AS1/E2F1 positive regulatory loop important for the promotion of BC malignant behaviors. The TMPO-AS1/E2F1 loop should be considered in the quest for new BC therapeutic options.